Enhanced electron field emission from NiCo2O4 nanosheet arrays - Naik, Kusha Kumar; Khare, Ruchita T.; Gelamo, Rogerio V.; More, Mahendra A.; Thapa, Ranjit; Late, Dattatray J.; Rout, Chandra Sekhar (Materials Research Express, 2015)
Electron emission properties of electrodeposited spinel NiCo2O4 nanosheet arrays grown on Ni foam have been studied. The work function of NiCo2O4 was calculated by density functional theory using the plane-wave basis set and used to estimate the field enhancement factor. The NiCo2O4 nanosheet arrays exhibited a low turn-on field of 1.86 V mu m(-1) at 1 mu A cm(-2) and current density of 686 mu A cm(-2) at 3.2 V mu m(-1), with field enhancement factor beta = 1460 and good field emission current stability. The field emission properties of the NiCo2O4 nanosheet arrays showed enhanced performance compared to chemically prepared NiCo2O4 nanosheets. Hence, the nanosheet arrays have great potential as robust high performance vertical structure electron emitters for future flat panel displays and vacuum electronic device applications.
Keywords: Density functional theory; field emission; nanosheets; NiCo2O4; spinel